EFFECT OF PROBLEM BASED LEARNING MODELS ON THE ABILITY TO REMEMBER ENGLISH VOCABULARY IN PRESCHOOL - Putri A.P.; Suparno S.; Issaliyeva S.; Issaliyeva S.; Retnawati H; Arpentieva M.R.; Kassymova G.K. (Scientific Journal of Pedagogy and Economics, 2020)
Early childhood is a fundamental period for the life of a human being, the selection of learning models in the world of education makes children active students. However, the active involvement of children is something that must still be considered in teaching and learning activities in Indonesia. Quasi-experimental research was conducted using 60 children aged 4-5 years, on the influence of the problem-based learning model on the ability to recognize English vocabulary in kindergarten. Bloom's Taxonomic thinking concept is a reference to children's ability to remember English vocabulary such as mentioning, identifying, showing, and pairing pictures using English. Comparison between the control class of 30 children and the experimental class with the number of 30 children was done in obtaining the results of a comparison of the effects generated on the learning model. The results showed that the ability to remember English vocabulary in the experimental class in the application of the problem based learning model increased significantly compared to the research control class. Differences in outcomes are likely to arise due to research interventions, for this reason further study is required by using a larger sample size of the study to obtain the accuracy of the effects caused by the application of the problem based learning model to the ability to remember English vocabulary in kindergarten and higher education levels. Further adjusted to the stages in the concept of higher Bloom Tasonomics thinking skills.